Effects of elevated emotional symptoms on metabolic disease development: a 10-year follow-up study - Sanchez-Carro, Yolanda; de la Torre-Luque, Alejandro; Vassou, Christina; Lopez-Garcia, Pilar; Georgousopoulou, Ekavi; Pitsavos, Christos; Ayuso-Mateos, José Luis; Panagiotakos, Demóstenes (Frontiers in Psychiatry, 2023)
Background: In recent decades, the relationship between emotional disorders (i.e., depression and anxiety) and alterations in physiological functions (i.e., inflammation or metabolism) have been well supported. However, studies on a symptom-based approach have provided mixed results. Our study aims to gain insight into how subclinical statuses, featured by elevated depressive and/or anxious symptoms, may influence immunometabolic alterations in the concurrent relationship; and the development of metabolic diseases at 10-year follow-up: diabetes, hypertension and hypercholesterolemia.Methods: Data from 758 Greek adults [394 men (aged 41±10 years) and 364 women (aged 37±12 years)] were used. Four groups were created according to the levels of depressive and anxiety symptoms: 1) control group (CG), 2) depressive group (DG), 3) anxiety group (AG) and 4) depressive and anxiety group (DAG). Multi-indicator multicauses (MIMIC) modeling was used to estimate metabolic function and inflammatory response scores, on a wide selection of blood biomarkers. Finally, a binary logistic regression was carried out to study the influence of symptoms on the development of the aforementioned metabolic diseases on a 10-year follow-up.Results: Group membership was not associated with metabolic function score.Conversely, DAG membership was related with higher inflammatory response score (B= .20, CI95= .01, .40), with respect to the CG (p < .05). Both age and sex were significant variables in the calculation of both scores.Regarding disease at 10-year follow-up effect, risk of developing diabetes, hypertension and hypercholesterolemia was associated with age and socioeconomic status. Moreover, DG membership was significant for diabetes risk (OR= 2.08, CI95= 1.00, 4.22) and DAG for hypercholesterolemia (OR= 1.68, CI95= 1.16, 2.43).Limitations: Data on antiinflammatory drugs and psychopharmacological medication were not collected in this study.Conclusions: Elevated symptoms of depression and anxiety accounts for inflammatory alterations at concurrent relationship and a higher risk of 10-year follow-up metabolic diseases.